Ethics and integrity in research with older people and service users : moving beyond the rhetoric - O'Sullivan, Roger (Advances in research ethics and integrity ;, 2023)
Featuring contributions from the US, Europe and the UK, this edited collection addresses issues relating to research ethics and integrity when undertaking social research with older people and service users. Setting out practical insights and guidance, as well as addressing theoretical and philosophical aspects, this volume includes contributions from 'researchers', 'the researched' and 'those in between' on topics including dementia, family carers, safeguarding and mental health with the common goal of producing high quality 'user' relevant research. Equipping readers with an understanding of how to move forward not only as researchers but also as consumers of research and citizens, Ethics and Integrity in Research with Older People and Service Users is a timely and insightful contribution to the Advances in Research Ethics and Integrity series.